PYCNODYSOSTOSIS AFFECTING ONLY THE MALE SIBLINGS OF A FAMILY – A RARE CASE REPORT - ANURADHA S; BHARATHI. K (International Journal of Pharma and Bio Sciences, 2012)
Pycnodysostosis is a rare genetic disorder with autosomal recesive mode of inheritance. It is characterised by short stature, stubby extremities, facial dysmorphism, frequent pathological fractures of long bones, open anterior fontanelles, blue sclera and absence of mental retardation. Here, we are presenting a rare case report of pycnodysostosis from Tamilnadu, India. In our case, pycnodysostosis is affecting all the male siblings of a family while sparing the female siblings. This rare case portrays non-classic type of inheritance of pycnodysostosis. This is the first case report in medical literature documenting non-classic pattern of inheritance in pycnodysostosis violating the mendelian law of inheritance.